Attraction is altered via modulation of the medial prefrontal cortex without explicit knowledge - Zorns, Samantha; Sierzputowski, Claudia; Ash, Sydney; Skowron, Molly; Minervini, Anthony; LaVarco, Adriana; Pardillo, Matthew; Keenan, Julian Paul (Frontiers in Human Neuroscience, 2024)
Previous studies have demonstrated that brain stimulation can alter an individual’s physical appearance via dysregulation of the Medial Prefrontal Cortex (MPFC). Here we attempted to determine if individuals who receive rTMS (repetitive Transcranial Magnetic Stimulation) delivered to the MPFC were rated more attractive by others. It has been previously reported that 1Hz (Inhibitory) TMS can alter one’s facial expressions such that frontal cortex inhibition can increase expressiveness. These altercations, detected by external observation, remain below the level of awareness in the subject themselves. In Phase I, subjects (N=10) who received MPFC rTMS and had their photographs taken after each of 5 stimulation conditions in addition to making self-ratings across a number of variables including attractiveness. In Phase II, participants (N=430) rated 5 pictures of each of the Phase 1 individuals on attractiveness. It was found that there was no significant differences in self-assessment following rTMS (Phase I). However, attractiveness ratings differed significantly in Phase II. There was a significant difference found between 10 Hz TMS delivered to the MPFC (p<0.001) such that individuals were rated as less attractive. Furthermore, 1 Hz TMS to the MPFC increased the number of ‘Most Attractive’ ratings while 10Hz TMS decreased the number of ‘Most Attractive’ ratings (p’s<.001). These results suggest that the MPFC plays a role in attractiveness to others. These data also support research that one’s appearance can be altered below the level of awareness via rTMS . To our knowledge, this is the first investigations to have examined how brain stimulation influences one’s attractiveness.